Kekuatan Pencairan Sepihak Terhadap Jaminan Deposito Milik Negara Pada Kredit Perbankan Berupa Cash Collateral Credit Di Bank X - Andrian Nathaniel; Tandyo Hasan; Jusup Jacobus Setyabudhi (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research discusses the power of unilateral execution carried out on state-owned collateral objects. There is a lot of gossip or uncertainty related to the status of state assets, in the sense that there are many legal rules that still intersect or overlap in defining state assets themselves. This overlapping of legal regulations has resulted in various interpretations regarding the extent to which the existence and definition of state assets can be applied, one of which is related to BUMN assets, whether they are included in state assets or not state assets. BUMN is a state-owned business entity which of course operates like a business entity in general, so that it carries out various legal and non-legal actions like business entities such as PT, CV, and so on. One of the BUMNs in the form of Persero took legal action by entering into a credit agreement in the form of cash collateral credit at BCA Bank, where it was discovered that the performance of the BUMN was starting to decline and of course this had an impact on the finances of the BUMN Persero itself, so this research will aim to provide a perspective on what the Bank can do if the state-owned company experiences default based on the applicable regulations. This research is using ‘normative-juridical’ as research type where the approach to the processing of legal materials is carried out by means of a literature review. Normative-juridical approach in this research used to analyse the power of unilateral execution of state-owned (BUMN) deposits in credit agreements with a cash collateral credit scheme at Bank X.